Economy of broiler production as influenced by stocking density, protein and energy levels, and season (2018)
This study was carried out to assess the effect of stocking density, protein and energy levels, and season on the economy of broiler production. In a 6x3x2 factorial arrangement using completely randomized design, six diets with three metabolisable energy (ME kcal;/kg) and two crude protein(%) levels combination: 3106.00 and 23.00 (control, diet 1); 3112.00 and 21.70 (Diet 2); 2928.00 and 23.40(Diet 3); 2933.00 and 21.90(Diet 4); 3227.00 and 23.10(Diet 5); 3230.00 and 21.80 (Diet 6), were formulated. Three stocking densities (birds per m2):10, Low SD (LSD); 12, Recommended SD(RSD); and 14, High SD (HSD), were used in Late Wet Season (LWS), August-November) and Late Dry Season(LDS, February-April). In a seven-week feeding trial, 576 one-week old broilers were assigned to the respective diets and stocking densities, at 32 birds per treatment, in each season. Live weight per m2 (LW/m2, kg), Feed cost per live weight (FC/LW, kg), Gross margin/m2 (GM/m2, N Total Variable Cost/m2 (TVC/m2), were assessed. Data were analyzed using descriptive statistics and ANOVA at α0.06.The LW/m2 was highest (p>0.05) for birds on HSD in both seasons. Birds on diet 4 had highest LW/m2 and lower FC/LW during LWS, while those on diet 1 had highest LW/m2 and lower FC/W during LDS. Birds raised on HSD had highest LW/m2 during both seasons, while those raised during LDS had highest Gm/m2. Late dry season (LDS), RSD&HSD had higher Gm/m2. Total Variable Cost was highest for LWS at HSD and least for LDS at LSD. Broiler production is more profitable during late dry season at stocking 14 birds/m2 with diet containing 3106 MEkcal/kg and 23.0% crude protein.